Applications of Artificial Intelligence and Deep Learning in Glaucoma. Issue 1 (12th January 2023) - Chen, Dinah; Ran, Emma Anran; Tan, Ting Fang; Ramachandran, Rithambara; Li, Fei; Cheung, Carol; Yousefi, Siamak; Tham, Clement C.Y.; Ting, Daniel S.W.; Zhang, Xiulan; Al-Aswad, Lama A.
Abstract : Diagnosis and detection of progression of glaucoma remains challenging. Artificial intelligence–based tools have the potential to improve and standardize the assessment of glaucoma but development of these algorithms is difficult given the multimodal and variable nature of the diagnosis. Currently, most algorithms are focused on a single imaging modality, specifically screening and diagnosis based on fundus photos or optical coherence tomography images. Use of anterior segment optical coherence tomography and goniophotographs is limited. The majority of algorithms designed for disease progression prediction are based on visual fields. No studies in our literature search assessed the use of artificial intelligence for treatment response prediction and no studies conducted prospective testing of their algorithms. Additional challenges to the development of artificial intelligence–based tools include scarcity of data and a lack of consensus in diagnostic criteria. Although research in the use of artificial intelligence for glaucoma is promising, additional work is needed to develop clinically usable tools.